2019
DOI: 10.1038/s41598-019-44399-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of trifluridine correlates with the thymidine kinase 1 expression level

Abstract: Trifluridine (FTD), a tri-fluorinated thymidine analogue, is a key component of the oral antitumor drug FTD/TPI (also known as TAS-102), which is used to treat refractory metastatic colorectal cancer. Thymidine kinase 1 (TK1) is thought to be important for the incorporation of FTD into DNA, resulting in DNA dysfunction and cytotoxicity. However, it remains unknown whether TK1 is essential for FTD incorporation into DNA and whether this event is affected by the expression level of TK1 because TK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…A representative selection of references with a high biosimilarity to DFO is depicted in Figure 4, including the kinase inhibitor roscovitine, [25] the nucleoside analogue trifluridine, [26] the DNA topoisomerase 1 inhibitor topotecan, the DNA intercalating agent doxorubicin and the iron chelator ciclopirox. Beyond the high biosimilarity to DFO (Figure 3), these references also exhibit a high compound cross‐similarity (Table S5) and define a CPA cluster based on a similar morphological phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A representative selection of references with a high biosimilarity to DFO is depicted in Figure 4, including the kinase inhibitor roscovitine, [25] the nucleoside analogue trifluridine, [26] the DNA topoisomerase 1 inhibitor topotecan, the DNA intercalating agent doxorubicin and the iron chelator ciclopirox. Beyond the high biosimilarity to DFO (Figure 3), these references also exhibit a high compound cross‐similarity (Table S5) and define a CPA cluster based on a similar morphological phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…[23] Thus, the biosimilarity of iron-chelating agents and nucleoside or folic acid analogues, topoisomerase-, MAP kinase p38-, CDK-, PARP-, LSD1-and MMP-2 inhibitors and the D1 dopamine receptor agonist in the CPA is most likely not based on modulation of a similar target, that is, by direct interaction with proteins, but rather on a same MoA, that is, induction of cell-cycle arrest. [23,24] A representative selection of references with a high biosimilarity to DFO is depicted in Figure 4, including the kinase inhibitor roscovitine, [25] the nucleoside analogue trifluridine, [26] the DNA topoisomerase 1 inhibitor topotecan, the DNA intercalating agent doxorubicin and the iron chelator ciclopirox. Beyond the high biosimilarity to DFO (Figure 3), these references also exhibit a high compound cross-similarity (Table S5) and define a CPA cluster based on a similar morphological phenotype.…”
Section: Identification Of References With High Biosimilarity To Dfomentioning
confidence: 99%
“…6C ( 23 25 ). Therefore, TK is a predictive factor for the efficacy of FTD ( 26 28 ). In the present study, 5FU-resistant LS174T/5FUR cells showed decreased sensitivity to FdUMP, and it appears to be difficult to overcome this type of 5FU resistance by 5FU derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of TK1 was examined in a study of colorectal cancer cell line HCT-116, which was knocked down for TK1 through CRISPR/Cas9 [ 27 ]. Compared with parental cells, cells without TK1 expression developed resistance to trifluridine/tipiracil.…”
Section: Biomarkers From Preclinical Modelsmentioning
confidence: 99%
“…Compared with parental cells, cells without TK1 expression developed resistance to trifluridine/tipiracil. In contrast, innate expression of TK1 in different colorectal cancer cell lines showed no correlation with trifluridine/tipiracil sensitivity, a fact that the authors attribute to different genetic backgrounds, which introduce additional and diverse molecular defects that could affect sensitivity [ 27 ]. Moreover, acquired resistance to trifluridine in the colorectal cancer cell line DLD1 is associated with loss of function of TK1 due to a point mutation in its gene, and resistance ensues in these cells through knockout of the gene through CRISPR/Cas9 [ 28 ].…”
Section: Biomarkers From Preclinical Modelsmentioning
confidence: 99%